What do we know about lobular cancer of female breast? - Jeziorski, Arkadiusz (Contemporary Oncology/Współczesna Onkologia, 2004)
Lobular carcinoma of the breast causes troubles both in diagnosis and in the treatment. This kind of cancer does not have its own classification of malignancy, and it is difficult to find proper prognostic and predictive factors. Also the treatment, especially the application of breast conserving therapy is controversial. The estimation of the prognosis in different forms of subtypes as well as the prognostic value of in situ form is still to be discussed. This paper summarizes what we know about lobular cancer of female breast.